Arbitrary waveform constant current stimulator for long-term wearable applications. (June 2019) - Breen, Paul P.; Serrador, Jorge M.; Gargiulo, Gaetano D.
Highlights: No suitable device exists for long-term noise stimulation. A new wearable, portable arbitrary waveform current stimulator was developed. The novel device provides the required intervention in a user-friendly manner. Abstract: Subsensory electrical noise stimulation has been shown to improve sensory perception in humans. However, the majority of this work has been limited to the laboratory due to unavailability of portable body-worn stimulators. In this paper, we present a robust and reliable stimulator, engineered for wearable applications and designed to extend modulation of human sensory perception outside the physiology laboratory. The stimulator provides an arbitrary waveform constant current stimulation, offering continuous current stimulation up to ±5 mA with a voltage compliance of ±25 V (expandable up to 70 V). A graphical user interface allows setting of stimulus parameters within fixed ranges via a USB connected computer. The interface is very simple using a single power switch and a single multi-coloured LED for device feedback. The applied stimulus voltage and current are continually monitored and used to detect short circuit, high impedance conditions. These conditions, and other errors e.g. low battery state, put the device in a safe state with the user disconnected via a relay. All captured data, including accelerometer data, is logged to a removable SD card. Powered by an interchangeable, Li-Ion battery pack >4 h stimulation is achievable. The full circuit, system software and bench tests performed are presented.